Non-Ischemic Cerebral Energy Dysfunction at the Early Brain Injury Phase following Aneurysmal Subarachnoid Hemorrhage - Laurent Carteron; Laurent Carteron; Camille Patet; Camille Patet; Daria Solari; Daria Solari; Mahmoud Messerer; Roy T. Daniel; Philippe Eckert; Reto Meuli; Mauro Oddo; Mauro Oddo (Frontiers in Neurology, 2017)
BackgroundThe pathophysiology of early brain injury following aneurysmal subarachnoid hemorrhage (SAH) is still not completely understood.ObjectiveUsing brain perfusion CT (PCT) and cerebral microdialysis (CMD), we examined whether non-ischemic cerebral energy dysfunction may be a pathogenic determinant of EBI.MethodsA total of 21 PCTs were performed (a median of 41 h from ictus onset) among a cohort of 18 comatose mechanically ventilated SAH patients (mean age 58 years, median admission WFNS score 4) who underwent CMD and brain tissue PO2 (PbtO2) monitoring. Cerebral energy dysfunction was defined as CMD episodes with lactate/pyruvate ratio (LPR) >40 and/or lactate >4 mmol/L. PCT-derived global CBF was categorized as oligemic (CBF < 28 mL/100 g/min), normal (CBF 28–65 mL/100 g/min), or hyperemic (CBF 69–85 mL/100 g/min), and was matched to CMD/PbtO2 data.ResultsGlobal CBF (57 ± 14 mL/100 g/min) and PbtO2 (25 ± 9 mm Hg) were within normal ranges. Episodes with cerebral energy dysfunction (n = 103 h of CMD samples, average duration 7.4 h) were frequent (66% of CMD samples) and were associated with normal or hyperemic CBF. CMD abnormalities were more pronounced in conditions of hyperemic vs. normal CBF (LPR 54 ± 12 vs. 42 ± 7, glycerol 157 ± 76 vs. 95 ± 41 µmol/L; both p < 0.01). Elevated brain LPR correlated with higher CBF (r = 0.47, p < 0.0001).ConclusionCerebral energy dysfunction is frequent at the early phase following poor-grade SAH and is associated with normal or hyperemic brain perfusion. Our data support the notion that mechanisms alternative to ischemia/hypoxia are implicated in the pathogenesis of early brain injury after SAH.